Improving Characteristics of Clayey Soil Using Basalt Fibre, Construction and Demolition Waste and Calcium Carbide - Akanksha Verma; Sharma, R.K. (International Journal of Sustainable Construction Engineering and Technology, 2023)
When exposed to changes in moisture, highly compressible clay soils usually show the characteristic of swelling and shrinking and have very poor strength properties. The infrastructures standing on such soil produce fractures as a result of this feature, making the buildings unstable and liable to collapse. By enhancing  the characteristics of clayey soils using soil stabilization can improve their engineering properties. The purpose of this paper tends to investigate the use of construction and demolition waste (C&D), basalt fibre (BF) and calcium carbide (CCR) for stabilization of highly compressible clayey soil. Several laboratory experiments including differential free swell (DFS), Atterberg limits, standard proctor and unconfined compressive strength (UCS) are conducted on soil alone and in combination with admixtures used. Based on UCS result, optimum percentages of C&D waste, basalt fibre and calcium carbide obtained were further tested for California bearing ratio (CBR). The findings show rising UCS and CBR values with addition of 21% C&D waste, 0.3% basalt fibre and 4% calcium carbide in combination to each other with clayey soil. The thickness for flexible pavement was developed using IITPAVE software for CBR values based on specifications of IRC: 37-2018. The software results revealed a decrease in pavement thickness for all combinations of commercial vehicle daily counts of 1000, 3000, and 5000. When clayey soil is combined with C&D waste (21%), BF (0.3%), and CCR (4%) in combination, the greatest reduction in subgrade layer thickness and cost is observed. This method not only improves the geotechnical characteristics of the subgrade layer, aids in decreasing the thickness of the pavement, is highly cost-effective, and resolves the issue of disposal of C&D waste and environmental degradation due to CCR.